Socio-Demographic Profile of Fatal Poisoning in a Tertiary Care Teaching Hospital of Coimbatore District-A Retrospective Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Poisoning poses a major public health problem mainly in developing countries. Because ofthe rapid industrialization and advancement in agricultural sector, fatality by poisoning also increases dayby day. The aim of this study is to determine the socio-demographic profile of fatal poisoning in CoimbatoreDistrict. Methods: This retrospective study was carried out in Department of Forensic Medicine, CoimbatoreMedical College, Coimbatore, Tamil Nadu with data obtained from fatal poisoning cases brought forpostmortem examination from January 2016 to December 2016. Identification of specific poisons were donewith chemical examiner’s report. All collected data were analyzed in various possible aspects in the preparedproforma. Results: During the study period the total number of medico legal autopsies conducted were 3675out of which fatal cases due to poisoning were 600(16.33%) cases. The study showed that the incidence ofpoisoning was more common among married men ie.303 cases (50.5%) out of 600 total number of poisoncases. The incidence was more common in the age group 31 – 40 years in males (86 cases) which formed14.3 % and in females it is 21-30 years (65 cases) which formed 10.8%.When we observed the religion wisedistribution, Hindu males out numbered 369 out of 600 cases which formed 61.5%. Conclusion: Morbidityand mortality due to poisoning can be minimized by health education, early referral, establishment oftoxicological units for detection of specific poisons and appropriate guidance for proper management ofpoisoning cases at hospitals and primary health care centers.